Adherence to combined lifestyle factors and their contribution to obesity in the IDEFICS study. (December 2015) - Kovács, E.; Hunsberger, M.; Reisch, L.; Gwozdz, W.; Eiben, G.; De Bourdeaudhuij, I.; Russo, P.; Veidebaum, T.; Hadjigeorgiou, C.; Sieri, S.; Moreno, L. A.; Pigeot, I.; et al.
Summary: Background: The Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS (IDEFICS) study investigated the aetiology of childhood obesity and developed a primary prevention programme. Methods: Pre‐intervention adherence to key behaviours related to childhood obesity, namely water/sweetened drink, fruit/vegetable consumption, daily TV time, physical activity, family time and adequate sleep duration, was measured at baseline. Adherence to international recommendations was converted into a composite score ranging from 0 (none) to 6 (adhering to all). Data on adherence were available for 7, 444 to 15, 084 children aged 2–9.9 years, depending on the behaviour. By means of multi‐level logistic regression models adjusted for age, sex and country, we calculated odds ratios (OR) and 95% confidence intervals (CI) to estimate the relationship between adherence to these recommendations and the risk of being overweight/obese. Results: Adherence ranged from 15.0% (physical activity) to 51.9% (TV time). As adherence increased, a lower chance of being overweight/obese was observed; adhering to only one key behaviour (score = 1) meant an OR = 0.81 (CI: 0.65–1.01) compared with non‐adherence (score = 0), while adhering to more than half of the key behaviours (score ≥ 4) halved the chance for overweight/obesity (OR = 0.54, CI: 0.37–0.80). Adherence to physical activity, TV and sleep recommendations was the main driver reducing the chance of being overweight. Overweight/obese children were more likely not to adhere to at least one of the recommended behaviours (19.8%) than normal‐weight/thin children (12.9%) Conclusion: The selected key behaviours do not contribute equally to a reduced chance of being overweight. Future interventions may benefit most from moving more, reducing TV time and getting adequate sleep. © 2015 World Obesity